Sneaky Snake: assessing metacognitive behavior in 5 to 6 year-olds with an unsolvable task - Buehler, Florian Jonas; Oeri, Niamh (Frontiers in Developmental Psychology, 2024)
In the present study, we developed an unsolvable behavioral metacognitive task for kindergarten children. The task was designed to gain insight into how children’s metacognitive processes, measured as monitoring (e.g., checking the plan) and control behavior (e.g., seeking a piece), operate in a problem-solving task that mimics real-life scenarios. Five to six-year-old kindergarten children (N = 72) were asked to build a wooden snake according to a plan. The middle piece of the snake (fourth out of seven pieces) was missing, making the task unsolvable. Other than expected, metacognitive behavior was not related to teacher ratings of metacognitive self-regulation. However, we found age differences. Children in kindergarten year two (M = 5.85 years old) showed more control behavior than children in kindergarten year one (M = 5.05 years old). Surprisingly, we did not find age differences in monitoring behavior. Lastly, we found that metacognitive behavior differed between the solvable part (before the missing piece is reached) and the unsolvable part (after the missing piece is reached). Children showed more monitoring and less control behavior in the solvable part than in the unsolvable part. The current study contributes to the metacognitive research methodology by capturing children’s metacognitive processes in action using an ecological-valid, unsolvable behavioral task.